RESOLUSI KONFLIK ETNIK SAMAWA DAN ETNIK BALI Dl SUMBAWA - Syaifudding Iskandar (Populasi, 2009)
This study aims to understand the background of conflict between Samawa ethnic and Balinese that still undercover for more than 25 years. The objective of this study are to explore the background of Balinese movement to Sumbawa, to identify the underlying causes of conflict between Samawa ethnic and Balinese and to address the conflict resolution that had been applied. The study applied qualitative approach. This study reported that the motivation of Balinese moved to Sumbawa were to increased their standard of live. Domination of the Balinese in social, economic, political and cultural aspects became the underlying factors of conflict between Balinese and Samawanes. Community based conflict resolution were applied through involving the community leaders from both side in coordination process and increased cultural communication for the shake of harmony and tolerance among society in Kabupaten Sumbawa.